Language in the bilingual brain: "age" vs. "stage" - Mildner, Vesna (2009)
There are a number of factors that may, to a varying extent, influence the representation of languages in a bilingual's brain. Some of the most frequently studied ones are: handness, gender, language characteristics, script, learning strategies and methods, age of acquisition, competence, frequency and conditions of use, etc. Age of acquisition ("age") and competence ("stage") have been customarily addressed in parallel, since there is usually a high correlation between the two: in a natural setting, it is expedcted that the longer one studies a foreign language (lower age of acquisition) the higher his/her competence. Of the two, the age of acquisition has been considered as more influential in view of its relatedness to neural pasticity. However, some recent studies have shown that keeping the age of acquisition constant it may, in fact, be competence that plays a more decisive role in cerebral representation of a bilingual's languages. The paper reviews arguments in favor of one or the other factor.